The Role of Strategic Management in Tourism Business Sustainability: A Case Study on Digital Economy-Based Tourist Destinations - Johni Eka Putra; Riri Cornelia; Hapsari Widayani; Anggi Oktaviani; Muhammad Aqshel Revinzky (SEULANGA SYSTEM PUBLISHER, 2025)
This study explores the role of strategic management in supporting tourism business sustainability within digital economy-based destinations, focusing on Ciletuh-Palabuhanratu Geopark in West Java, Indonesia. The research aims to determine whether differences in the level of digital-based strategic management among tourism actors influence their sustainability performance. Using a quantitative approach, data were collected from 90 respondents categorized into three groups: low, moderate, and high digital strategy adopters. A one-way ANOVA test was conducted to examine whether significant differences existed in the economic, social, and environmental dimensions of sustainability among the groups. The results show a statistically significant difference in sustainability outcomes, with businesses in the